USLUB AT TASYKHISH FI AL QUR’AN AL KARIM WA ATSARUHU FI AL MUJTAMA’ AL ISLAMY - Muhammad Sa'i (Universitas Islam Negeri Mataram, 2023)
One of the characteristics of the Qur’an is its skill in articulating speech, which made eloquent Arabs prostrate themselves to its eloquence. This noble book was revealed in stunning ways that touch the Arabs' being, capture their hearts and entertain their minds. This message is intended to reveal the secrets of the Qur’an and its hidden purposes in diagnosing the meanings of the abstract and inanimate objects of great bodies. The main question of this research is why does God personify abstract meanings and inanimate objects in the Qur’an? Did he achieve the ultimate purpose of this book, the religious purpose? And in the method of analysis, it is a qualitative descriptive method that comes from the depth of reflection and contemplation. The results of this study are: 1) The Qur’an has attained the highest level of eloquence and rhetoric, and its diagnosis of abstract and natural meanings, in order to stimulate conscience and emotion and awaken the mind and heart to reflect and contemplate. economic, political and others. Rather, he called for a new opinion and a new presentation that suits the era and the need to absorb the problems of contemporary man through his eloquent style.